Facial manifestations of Epstein–Barr virus‐related lymphoproliferative disease in childhood acute lymphoblastic leukemia in remission: Two atypical presentations. Issue 11 (8th July 2016) - Lu, Benjamin Y.; Kojima, Lisa; Huang, Mary S.; Friedmann, Alison M.; Ferry, Judith A.; Weinstein, Howard J.
Abstract: Epstein–Barr virus‐related lymphoproliferative disease (EBV‐LPD) rarely occurs in patients with acute lymphoblastic leukemia (ALL), who have not received hematopoietic transplantation. We describe EBV‐LPD manifesting as facial lesions in two children with ALL in remission. One patient was a 16‐year‐old male with T‐cell ALL with an EBV‐positive angiocentric polymorphous lip lesion presenting as right‐sided facial swelling. The other patient was a 12‐year‐old male with B‐cell ALL with an EBV‐positive polymorphous lymphoplasmacytic infiltrate presenting as bilateral dacryoadenitis. Neither patient had known primary immunodeficiencies. Both cases improved with immunosuppressant de‐escalation. These cases suggest that immunosuppression induced by maintenance chemotherapy is sufficient to promote EBV‐LPD.